2016
DOI: 10.2147/copd.s107409
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating PAI-1 levels are related to lung function decline, systemic inflammation, and small airway obstruction in chronic obstructive pulmonary disease

Abstract: BackgroundPlasminogen activator inhibitor-1 (PAI-1) and soluble urokinase-type plasminogen activator receptor (suPAR) participate in inflammation and tissue remolding in various diseases, but their roles in chronic obstructive pulmonary disease (COPD) are not yet clear. This study aimed to investigate if PAI-1 and suPAR were involved in systemic inflammation and small airway obstruction (SAO) in COPD.MethodsDemographic and clinical characteristics, spirometry examination, and blood samples were obtained from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
3
23
2
Order By: Relevance
“…Interestingly, this study found the highest PAI-1 levels in patients with GOLD Stages II and III. This observation is in good agreement with the finding of the previous study showing a significant association between higher levels of PAI-1 and airflow limitation in patients with predominantly mild-to-moderate COPD 15. Moreover, it was also found that triglycerides and hs-CRP are the best predictors for elevated PAI-1 levels in COPD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, this study found the highest PAI-1 levels in patients with GOLD Stages II and III. This observation is in good agreement with the finding of the previous study showing a significant association between higher levels of PAI-1 and airflow limitation in patients with predominantly mild-to-moderate COPD 15. Moreover, it was also found that triglycerides and hs-CRP are the best predictors for elevated PAI-1 levels in COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…There are two very recent studies showing an association between elevated PAI-1 levels and COPD, but considered neither comorbidities of COPD nor the whole spectrum of airflow limitation, from mild to very severe stage 14,15. The present study is the first to demonstrate that higher serum PAI-1 levels in COPD are independent of a broad spectrum of possible confounders, in particular established variables indicating metabolic and cardiovascular dysfunction.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In stable disease, Can et al reported higher serum suPAR levels compared to controls [ 14 ]. This contradicts a study by Wang et al who did not find significant difference between COPD and those in a healthy condition [ 15 ]. The discrepancy may be due to the relatively mild disease severity of the latter study [ 15 ], as the former study assessed patients with a wider range of lung function [ 14 ].…”
Section: Introductioncontrasting
confidence: 82%
“…This contradicts a study by Wang et al who did not find significant difference between COPD and those in a healthy condition [ 15 ]. The discrepancy may be due to the relatively mild disease severity of the latter study [ 15 ], as the former study assessed patients with a wider range of lung function [ 14 ]. In addition, a number of factors which characterize disease burden apart from lung function, including symptom burden, exacerbation history and arterial stiffness, has not been assessed.…”
Section: Introductioncontrasting
confidence: 82%